A Case of Pyriform Sinus Fistula Infection with Double Tracts - Masato Shino; Yoshihito Yasuoka; Kyoko Nakajima; Kazuaki Chikamatsu (Case Reports in Otolaryngology)
Pyriform sinus fistula is a rare clinical entity and the precise origin remains controversial. The fistula is discovered among patients with acute suppurative thyroiditis or deep neck infection of the left side of the neck and is usually located in the left pyriform sinus. To the best of our knowledge, only a single tract has been reported to be responsible for pyriform sinus fistula infection. We present a case of a 13-year-old female patient with a pyriform sinus fistula that caused a deep infection of the left side of the neck and showed double-tract involvement discovered during surgical resection of the entire fistula. Both tracts arose around the pyriform sinus and terminated at the upper portion of the left lobe of the thyroid.